Error culture, auditors' error communication, and the performance of the auditee: A~study among German local public sector auditors - David Lindermüller; Irina Lindermüller; Christian Nitzl; Bernhard Hirsch (Schmalenbach Journal of Business Research (SBUR), 2024)
In the course of financial and value for money audits, public sector auditors are facing different types of errors: accounting and economic errors, respectively. This study examines the relations between error culture in public sector audit organizations, auditors' communication of accounting and economic errors, and performance of the auditee. The analyses of survey data from German local public sector auditors show that a~strong error culture within the audit organization positively affect the auditors' communication of errors to the auditee, regardless of the error type. Additionally, a~strong error culture positively mediates the performance of the audited institution through the auditors' communication of economic errors. This implies that it is important for public sector audit organizations to build a~strong error culture. In addition to its practical contrition, the study provides novel theoretical insights as it demonstrates that the error management of one organization (audit entity) matters for the performance of another organization (audited entity).
Keywords: 650; Error communication; Financial audits; Partial least squares-structural equation modeling; Value for money audits